Wrath, Sadness, Vengeance and Compassion: Achilles Facing Death - Rodríguez López, María Isabel (Eikón / Imago, 2021)
Any approach to the figure of Achilles is an encounter with sadness and death, with a diversity of deaths, and also, with the emotional human response to them. In this paper, we will analyse the iconography of some of the most outstanding themes in relation to the hero’s deeds: the death of Troilus, the death of Patroclus and the death of Hector, starting from the prototypes forged in ancient art and observing the main iconic modifications occurred over time.